13(5-2x)=-13(4x+1)-8x

Simple and best practice solution for 13(5-2x)=-13(4x+1)-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(5-2x)=-13(4x+1)-8x equation:


Simplifying
13(5 + -2x) = -13(4x + 1) + -8x
(5 * 13 + -2x * 13) = -13(4x + 1) + -8x
(65 + -26x) = -13(4x + 1) + -8x

Reorder the terms:
65 + -26x = -13(1 + 4x) + -8x
65 + -26x = (1 * -13 + 4x * -13) + -8x
65 + -26x = (-13 + -52x) + -8x

Combine like terms: -52x + -8x = -60x
65 + -26x = -13 + -60x

Solving
65 + -26x = -13 + -60x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '60x' to each side of the equation.
65 + -26x + 60x = -13 + -60x + 60x

Combine like terms: -26x + 60x = 34x
65 + 34x = -13 + -60x + 60x

Combine like terms: -60x + 60x = 0
65 + 34x = -13 + 0
65 + 34x = -13

Add '-65' to each side of the equation.
65 + -65 + 34x = -13 + -65

Combine like terms: 65 + -65 = 0
0 + 34x = -13 + -65
34x = -13 + -65

Combine like terms: -13 + -65 = -78
34x = -78

Divide each side by '34'.
x = -2.294117647

Simplifying
x = -2.294117647

See similar equations:

| 9y+3y+48=180 | | 9x+3=2x+15 | | 7-2n=n-24 | | 3/5(10x-15)=27 | | 5-3(2x-7)=4(x+5)-6 | | -12+4(-3-x)=32-49 | | (5x+3y)(5x-3y)= | | 1.666d+.666=.25(d-2) | | 8x+3.1=-6+14.3 | | 1.666d+666=.25(d-2) | | 43+x=7 | | 14+2(y+3000)=1340 | | -49=6x-13-4c | | d+32=1400 | | -0.8=.13x-.21x | | 30+3y-7=10y-12-2y | | 4x+2+2x=4x+4x | | f-11=987 | | 1.666+.666=.25(d-2) | | x+6x=46207 | | 2x+y+10x-4y=180 | | 99x=3 | | 0=4x^3-6x^2+1 | | by+2=c | | 36-4=-13 | | -3(4m+3)-5=-30-8m | | y^2-6x+27=0 | | x+19+3x=-5-3x-11 | | 4w+9=9w-7 | | A=4(3.14r^2) | | -122-x=-8x+32 | | t+56=96 |

Equations solver categories